SOSIOLOGI KAUM SUFI: Sebuah Model Studi Integratif-interkonektif - Dudung Abdurahman (Jurnal Sosiologi Reflektif, 2015)
This paper employs an integrated-interconnected perspective to examine Sufi groups and theirroles in developing Islamic teachings and performing social functions. Known as communities primarily characterized by their esoteric religious interpretation and Teacher- Student structured relationship, Sufi groups can be approached through analyzing their religious doctrines as well as their social practice. Combining these two analytical approaches, this paper argues that the dynamics of Sufi groups rests up on three factors. Firstly, the development of Sufi doctrines into ritual practices serves toproduce and strengthen particular patterns of social solidarity among the followers. Secondly, the participation of Sufi groups in the life of plural societal relations may take form in a distinct social movement, particularly when they are involved in the so-calledpublic spiritual and morality enforcement.Thirdly, Sufi groups can be classified into three groups: pragmatic-inclusive, fundamentalistexclusive, orpragmatic-fundamentalist.